What collaborative planning practices lack and the design cycle can offer: Back to the drawing table. (February 2021) - van Dijk, Terry
This article critically discusses the premises underpinning the collaborative ideal, which has become central to Western spatial planning practices. With their emphasis on a structure which focuses on the problem, actors, deliberation, agreement and acceptability, collaborative processes produce conservative choices. However, this approach might not effectively address the big challenges confronting our metropolitan areas and regions today. Instead, the essence of choosing how to respond in the face of long-term challenges is a thorough analysis of the situation (beyond just the actors' wishes), generation of a wide array of possible actions (more creative than mere compromises), and arriving at decisions which demonstrate vision and leadership. This resembles the design cycle, which we claim enriches the collaborative model. We propose principles for a more creative governance which suggest emphasizing the exploitation of an area's full potential instead of solving its specific problems.